Pragmalinguistic Features of the Speech of Russian-Speaking Students in the Period of Early Adulthood (Proceedings of Southern Federal University. Philology, 2019)
Elizaveta A. Sidorenko, Galina G. Matveeva (Rostov-on-Don,Russian Federation)This work is devoted to the pragmalinguistic component of students’ speech. The purpose of the study is to determine this component in the speech of communicants in a speech event. Analysis of various approaches to the age-related periodization of this group of subjects allowed us to dwell on the period of early adulthood and to conduct a study of their verbal behavior. The hypothetical deductive method, the method of quantitative calculation, the method of linguistic observation and description, the method of pragmalinguistic experiment were used during the process. Students’ social and humanitarian directions selected from social networks were used as a factual material. The data obtained in the digital and percentage are presented in the table. Individual number of small syntactic groups, actualization of speech plans, absolute speech indicator were identified. The average speech indicator is shown, which reflects the stereotypical speech behavior of the student’s language group. In the conclusions, the individual socio-specific features of the speech behavior of this group of students are clearly expressed.Key words: pragmalinguistics, speech, speech behavior, students’ speech behavior, growing period, social behavior of a person.DOI 10.23683/1995-0640-2019-4-72-79